The Information Strategic Planning for Majlis Perbandaran Sungai Petani Kedah - Mohd Yusri, Mohamad Yusop (2010)
To enable an organization advanced in terms of ICT implementation and the IS organization, it is necessary to a sound and complete ISP. The purpose of this study was to develop a strategic information plan that will be adopted by the Majlis Perbandaran Sungai Petani Kedah as a reference for the future in terms of overall ICT development. Methodology used in this study is based on the recommendations of MAMPU. MAMPU has introduced its guideline to all government agencies to adopt the strategic plan to guide in the development of their information strategic plan. Using this methodology, it is expected to assist the Majlis Perbandaran Sungai Petani Kedah to identify the current state of the ICT environment of the problems being faced and recommend improvements to the ICT environment to facilitate ICT implementation at the Majlis Perbandaran Sungai Petani Kedah. Therefore, it is expected that the ISP is produced from this study can be fully implemented as a guidance to further develop ICT for the Majlis Perbandaran Sungai Petani Kedah.